Structural behaviours of circular hollow section T-joints subjected to elevated temperature - Nguyen, Minh Phuong. (2013)
The research on structural behaviour of circular hollow section (CHS) joints at elevated temperatures was motivated by the need of fire resistance estimations for performance-based approach of tubular structures. This thesis presents a study on structural behaviour of CHS T-joints in four parts where a set of CHS T-joints subjected to (i) brace axial compression; (ii) in-plane bending; and (iii) a standard ISO-834 fire curve. Test observations and failure mechanisms in the first three parts provide an input for the fourth part (iv) where an analytical model of CHS T-joint was developed using yield line approach.